ANALISIS KOMODITAS HORTIKULTURA UNGGULAN DAN SEBARANNYA DI WILAYAH KECAMATAN SE- KOTA TARAKAN - , SHINTA ARIANASOFA, Prof. Dr. Ir. Dwidjono Hadi Darwanto, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aimed to determine prospective horticulture commodities at each district that will be developed to be main commodity in Tarakan City in the future, and to determine pattern of distribution of horticulture commodities in each district of Tarakan City. This research used secondary data in form of harvest area, production, and product value of horticulture commodities in period of 2008-2012. Analytical tool used to determine prospective horticulture commodities are Location Quotient, Shift-share, and Klassen Typology. All of analysis result then collected and summarized by overlay methode. Analysis tools used to determine the distribution pattern of horticultural commodities is Locality Coefficient, and Specialization Coefficient. The result of overlay analysis indicated that there are differences in horticulture commodities at each district. The prospective horticultural commodities currently in each district are as follows: - Tarakan Timur : mustard , banana, mango, breadfruit and terap. - Tarakan Tengah : long beans, big chili, small chili, tomato, green beans, cucumber, and bitter melon. - Tarakan Barat : squash, papaya and rambutan - Tarakan Utara : spring onion, big chili, eggplant, cucumber, bitter melon, squash, kale, spinach, pumpkin, papaya, oranges, pineapple, watermelon and breadfruit. The results of the distribution analysis showed the commodities distributed equally at each district and pursue various horticultural commodities or do not have specialization in certain commodities.